Influence of Information Communication Technologies on University Administration in Nigeria - Jacob, Ogunode Niyi (European Journal of Life Safety and Stability (2660-9630), 2022)
This study investigate the influence of information communication technologies on university administration in Nigeria using three public higher institutions as a case study. The study adopted descriptive survey method for the study. The population of the study consists of three hundred staff of public federal higher institutions in North east geo political zone Nigeria. Questionnaire was used to collect data for the study. Sampling technique was adopted and stratified simple random technique. Staff status formed the basis of stratification while the lottery method constituted the basis of randomization. The research data were analyzed using percentage, mean and standard deviation and chi-square statistic. Result obtained showed there was significant relationship between information communication technologies and university administration. Information communication technologies influences teaching, research and community services programme of the universities positively. The result also revealed that inadequate fund, inadequate ICT infrastructural facilities, unstable power, unstable internet services, poor implementation of ICT policies, shortage of ICT staff, poor ICT literacy of staff were identified as problems hindering ICT usage in the universities in Nigeria. Based on this findings, the study recommended that the government should fund the public universities adequately to enable them acquire necessary ICT facilities needed for the administration of the universities.